Review of National HIV/AIDS Strategies for Countries Participating in the World Bank’s Africa Multi-Country AIDS Program - Mullen, Patrick (World Bank, Washington, DC, 2021)
The overall development objective of the World Bank's Multi-Country HIV/AIDS Program (MAP) for the Africa Region is to increase access to HIV/AIDS prevention, care, and treatment programs, with emphasis on vulnerable groups. The specific development objectives of each country project are to be drawn from the national strategic plans. Accordingly, "satisfactory evidence of a strategic approach to HIV/AIDS" is one of four eligibility criteria. This is to be demonstrated by "a coherent, national, multi-sector strategy and action plan for HIV/AIDS prevention, care, and treatment that has been developed through a participatory approach using social assessment techniques. It could also be demonstrated by having a participatory strategic planning process underway, with a clear roadmap and timetable" Accordingly, the objective of this review is to assess the extent to which national HIV/AIDS plans represent a strategic approach to addressing the epidemic. Evidence of a strategic approach includes: clear goals; explicit priorities; systematic planning, targets, timeframes, and indicators; clear plans for monitoring and evaluation; clearly specified implementing actors and responsibilities; and cost estimates and strategies for resource mobilization. Additional characteristics of a strategic approach are the extent to which plans are efficient, equitable, relevant, and feasible. National HIV/AIDS strategic plans from 21 of the 23 Sub-Saharan African countries participating in the MAP as of July 2003 are reviewed. Table 1 lists the countries, their populations and GNP per capita, estimated HIV prevalence (given in the plans), and timeframes of the plans. Appendix A1 lists the national strategies reviewed.